A study on customer retention in relation to service by cooperative provider in Takaful Ikhlas / Mohd Asyraf Abd. Rahman - Abd. Rahman, Mohd Asyraf (Faculty of Business and Management, 2011)
Customer retention defines as when company are successful in keeping their customer to still using their product or services rather than change to their competitors product or services. Customer retention also is important for most of the company to be prime mover and to sustain their profitability. That is, product or service must fulfill customer need and expectation. Corporate business department was operated since earlier establishment of Takaful Ikhlas Sdn Bhd (TISB). This department is focusing more on corporate sector and separated into three channel. Channel in this department comprises of cooperative, direct and corporate agent. Cooperative is a body established for various function mainly for their members such as for the purpose of financing, transportation, insurance and Takaful, services and others. Cooperative is able to generate a profit and expand the business since them running for both profit and benefit oriented. Nowadays, for the purpose of protection against unfortunate event, almost all cooperative prepare their members with insurance or Takaful. Takaful is Islamic insurance whereby it is a form of contribution from all members sharing a same risk into pooling system. There are many type of product of Takaful usually taken by cooperative for their members such as Group Term Takaful (GTT), Group Credit Term Takaful (GCTT), Group Personal Accident (GPA), motor Takaful Group Hospital and surgery and others. Customer retention is the key components in maintaining a profitable business for any organization. The aim of the study is to identify the factors that influence customer retention in relation to service by cooperative provider in Takaful Ikhlas Sdn Bhd.